Assessing the relationship between Body Mass Index and Bone Mineral Density in a clinical-based sample of Vietnamese aged 20–50: A generalized linear regression analysis - Trong Hung Nguyen; Thi Thuy Bui; Quang Duc Tran; Thi Hang Diem; Tuyet Mai Truong; Hong Truong Nguyen; Danh Tuyen Le (Human Nutrition & Metabolism, 2024)
Background: While some evidence has shown that the BMI component differentially influences bone mineral density (BMD), no studies have examined the association between BMI and BMD in Vietnamese adults. The objective of the present study was to examine the associations between BMI and BMD in relatively healthy Vietnamese adults. Demographic data, anthropometric measurements, BMD results measured by DXA and risk factors associated with BMD were retrospectively obtained from the medical records of 333 customers at the National Institute of Nutrition, Vietnam. The customers (aged 20–50 years) underwent a nutrition evaluation and completed BMD examinations between January 1 and November 30, 2021. Osteopenia was defined as the BMD (Z-score) < -2. The correlation between BMI and BMD was analyzed using generalized linear regression. The study found that 7.7% of females and 4.6% of males had osteopenia at the lumbar spine, while 6.9% of females and 5.7% of males had osteopenia at the total hip. Our study discovered a significant relationship between BMI and normal BMD or osteopenia among both males and females, except for the lumbar spine in males. Notably, the results indicated that underweight individuals had a higher likelihood of developing osteopenia. Furthermore, the positive correlation between being overweight or obese and having a higher BMD was also confirmed.Our findings show that the BMI categories affect BMD differently and that being underweight increases the risk of osteopenia among 20-50-year-old Vietnamese. Therefore, we emphasize the need for a BMI-based pre-screening tool for osteopenia in this age group before the further examination.